Less than Nations : Central-Eastern European Minorities after WWI, Volume 2. - Motta, Giuseppe, 1977- (Cambridge Scholars Publishing, 2013)
Less than Nations: Central-Eastern European Minorities after WWI represents the result of research that the author has carried over recent years, and was facilitated by the 2008 PRIN project (Programmi di Ricerca di Rilevante Interesse Nazionale) and the 2010 Sapienza Research funds. The book analyses the conditions of national minorities after World War I, when the geo-political map of Central-Eastern Europe was redefined by international diplomacy. The new settlements were based on the prin ...
Keywords: Minorities -- Europe, Eastern -- History -- 20th century.; Minorities -- Europe, Central -- History -- 20th century.; World War, 1914-1918 -- Influence.; Europe -- History -- 1918-1945.; Europe -- Politics and government -- 1918-1945.; Guerre mondiale, 1914-1918 -- Influence.; Europe -- Histoire -- 1918-1945.; Europe -- Politique et gouvernement -- 1918-1945.; European history.; International relations.; 20th century history: c 1900 to c 2000.; HISTORY -- Europe -- Western.; Influence (Literary, artistic, etc.); Minorities; Politics and government; Europe; Central Europe; Eastern Europe; 1900-1999; History